1992
DOI: 10.1017/s0022112092002787
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of three-dimensionally evolving jets under helical perturbations

Abstract: We study the three-dimensional evolution of a nominally axisymmetric jet subject to helical perturbations. Our approach is a computational one, employing an inviscid vortex filament technique to gain insight into the vorticity dynamics of jets dominated by helical vortices. For the case of a helical perturbation only, the streamwise vorticity forming in the braid is of the same sign everywhere, with the vortex helix representing streamwise vorticity of opposite sign. Owing to the helical symmetry, concentrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 38 publications
0
17
1
Order By: Relevance
“…In a high swirl number flow where the azimuthal velocity is comparable to the axial velocity, vortex breakdown may take place. Several important studies on swirling flow instabilities and coherent vortex motions, including experimental investigations [128][129][130][131][132][133], theoretical analyses [134][135][136][137][138], and numerical simulations [139][140][141][142][143][144], have been recently reported. Liang and Maxworthy [133] performed a notable experimental study of swirling jets, in which swirl is generated using a long rotating tube.…”
Section: • Lows Wirl Numbermentioning
confidence: 99%
“…In a high swirl number flow where the azimuthal velocity is comparable to the axial velocity, vortex breakdown may take place. Several important studies on swirling flow instabilities and coherent vortex motions, including experimental investigations [128][129][130][131][132][133], theoretical analyses [134][135][136][137][138], and numerical simulations [139][140][141][142][143][144], have been recently reported. Liang and Maxworthy [133] performed a notable experimental study of swirling jets, in which swirl is generated using a long rotating tube.…”
Section: • Lows Wirl Numbermentioning
confidence: 99%
“…For the nonswirling top hat jet velocity profile it is known that axisymmetric and helical perturbations will result in the formation of vortex rings or helices, respectively, all of the same sign. 28,29 For purely swirling flow, on the other hand, Caflisch et al 21 demonstrated that axisymmetric perturbations lead to the emergence of counter-rotating vortex rings. By superimposing a top hat streamwise velocity profile upon the purely swirling flow, we hence expect a breaking of the symmetry exhibited by the purely swirling flow alone.…”
Section: ͑1͒mentioning
confidence: 99%
“…22,[28][29][30][31][32] It is based on the theorems of Kelvin and Helmholtz and follows the general concepts reviewed by Leonard 33 and Meiburg. 34 A detailed account of the technique is provided in these earlier references.…”
Section: ͑1͒mentioning
confidence: 99%
“…Cotke and Kusek 6] showed that the helical modes pair in the manner discussed by Cohen and Wygnanski 5]. The temporal evolution of a cylindrical jet-like mixing layer excited by axisymmetric and helical disturbances with an additional azimuthal disturbance is numerically studied by Martin and Meiburg 19,20].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, a temporally-evolving calculation such as Martin and Meiburg 19,20] does not include the e ect of feedback from the downstream vortex structures. We are in the opinion that the rapid development of the three-dimensional structures in the early part of the shear layer of the unforced jet (Figs.…”
mentioning
confidence: 99%